The role of imaging in defining cardiovascular risk to help cancer patient management: a scoping review - Roberto Farì; Giulia Besutti; Pierpaolo Pattacini; Guido Ligabue; Francesco Piroli; Francesca Mantovani; Alessandro Navazio; Mario Larocca; Carmine Pinto; Paolo Giorgi Rossi; Luigi Tarantini (Insights into Imaging)
Abstract Objective This scoping review explores the potential role of cancer-staging chest CT scans in assessing cardiovascular (CV) risk in cancer patients. It aims to evaluate: (1) the correlation between non-gated chest CT and the conventional Agatston score from cardiac CT; (2) the association between coronary calcium scores from non-gated chest CT and CV risk in non-oncological patients; (3) the link between coronary calcium assessed by non-gated chest CT and CV events or endothelial damage in cancer patients. Methods Three different searches were performed on PubMed, according to the three steps described above. Both original articles and systematic reviews were included. Results Many studies in the literature have found a strong correlation between coronary calcium scores from non-gated chest CTs and the conventional Agatston scores from gated cardiac CTs. Various methodologies, including Agatston scoring, ordinal scoring, and the “extent” and “length” methods, have been successfully adapted for use with non-gated chest CTs. Studies show that non-gated scans, even those using iodinated contrast, can accurately assess coronary calcification and predict CV risk, with correlations as high as r = 0.94 when compared to cardiac CTs. In oncological settings, studies demonstrated a significant link between coronary calcium levels on non-gated chest CTs and higher CV risk, including MACE and overall mortality. Conclusions Radiological assessment of coronary calcium on non-gated CT scans shows potential for improving CV risk prediction. Critical relevance statement Non-gated chest CT scans can detect endothelial damage in cancer patients, highlighting the need for standardized radiological practices to assess CV risks during routine oncological follow-up, thereby enhancing radiology’s role in comprehensive cancer care. Key Points Cancer therapies improve outcomes but increase cardiovascular risk, requiring balanced management. Coronary calcification on non-gated CT correlates with Agatston scores, predicting cardiovascular risk. Routinely performed CTs predict cardiovascular risk, optimizing the management of cancer patients. Graphical Abstract